2015
DOI: 10.2147/tcrm.s73379
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally inserted central catheter thrombosis incidence and risk factors in cancer patients: a double-center prospective investigation

Abstract: BackgroundPeripherally inserted central catheters (PICCs) are widely used in chemotherapy, but the reported PICC thrombosis incidence varies greatly, and risks of PICC thrombosis are not well defined. This study was to investigate the incidence and risk factors of PICC-related upper extremity vein thrombosis in cancer patients.MethodsThis was a prospective study conducted in two tertiary referral hospitals from May 2010 to February 2013. Cancer patients who were subject to PICC placement were enrolled and chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 17 publications
(24 reference statements)
0
35
1
Order By: Relevance
“…Patients with ports can conduct activities such as swimming and have more positivity in terms of body image than other CVCs 4. PICCs offer many advantages such as avoiding CVC placement-associated mechanical complications such as pneumothorax and hemorrhage, and the professional nurse PICC teams have made their use more accessible in oncology departments 5. In China, the NTCs in the internal jugular vein or subclavian vein cost less than other CVCs and are used when the chemotherapy process is short.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ports can conduct activities such as swimming and have more positivity in terms of body image than other CVCs 4. PICCs offer many advantages such as avoiding CVC placement-associated mechanical complications such as pneumothorax and hemorrhage, and the professional nurse PICC teams have made their use more accessible in oncology departments 5. In China, the NTCs in the internal jugular vein or subclavian vein cost less than other CVCs and are used when the chemotherapy process is short.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that a study on PICCs implantation in tumor patients has shown that the incidence of UEDVT ranges from 4% to 50%. 18,19 All twelve cases of CVCs' malfunction did not render the line ineffective, such as the impossibility of injection and/or aspiration, but had made them difficult. According to the"Catheter Injection and Aspiration" (CINAS) classification scheme, we scored 6 2IN1ASI catheters' malfunctions, 4 IN2ASI catheters' malfunctions and 2 catheters with a IN2AS2 malfunction.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of them were listed in ( Supplementary Table 3 ). 7 studies compared PICC with CICC or Port ( n = 2872) [ 22 , 51 , 57 , 61 , 62 , 66 , 67 ], only 1 study involving mortality information [ 61 ], whereas 23 included studies which just displayed PICC without a comparison group ( n = 5824) [ 21 , 23 , 26 – 29 , 33 36 , 38 , 41 , 45 , 47 , 52 56 , 58 , 59 , 63 , 68 ]. 15 articles ( n = 6579) showed the details of CICC with pharmacological deep venous thrombosis (DVT) prophylaxis compared with placebo or other drugs, such as heparin drugs, warfarin and other thrombolytic drugs [ 24 , 25 , 30 32 , 37 , 39 , 40 , 42 44 , 46 , 49 , 50 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our meta-analysis, 23 included studies about PICC without a comparison group ( n = 5824) were just displayed by a forest plot showing the pooled, unweighted frequency of patients with peripherally inserted central catheter venous thromboembolism (VTE), which can be seen in (Figure 2 ) [ 21 , 23 , 26 – 29 , 33 36 , 38 , 41 , 45 , 47 , 52 56 , 58 , 59 , 63 , 68 ]. For these studies, the unweighted frequency of vein thrombosis was 9.2% (536/5824), which is higher than the former reported result 4.48% (189/4223) related to non-tumor and tumor mixed populations [ 69 ].…”
Section: Discussionmentioning
confidence: 99%